Edukasi Kesehatan Dan Praktik Pertolongan Pertama Siswa Yang Mengalami Syncope Pada Siswa Sekolah Dasar - Amila, Amila; Marbun, Agnes Silvina; Sembiring, Evarina (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Syncope (fainting) is a state of unscioousness in a person. Complete loss of conciousness Syncope (fainting) is a state of unconsciousness in a person. Complete loss of consciousness, in which both the person's hearing, sight and feeling stop completely. Elementary school children are an appropriate period to teach how to perform first aid to someone who has syncope, so that they can provide first aid if they see friends or family experiencing syncope. The purpose of this community service is to improve first aid efforts for students who have fainted with training targets aimed at teachers and students. The activity method is carried out by lectures and training in first aid practices for syncope. Evaluation by giving a questionnaire during the pretest and posttest. The results of this activity showed that the majority of knowledge about first aid who experienced syncope before being given education was lacking as much as 88%. After being given education, the majority of knowledge about first aid who experienced syncope was good as much as 64%. The school hopes that the activities that have been carried out will be sustainable, especially education and training for students and teachers regarding the importance of breakfast and choosing a nutritional menu for students in order to reduce the incidence of fainting.